Superplasticizer and hydrated lime for high-strength concrete - Kosim, Kosim; Fikri, Julian (Jurnal Teknika, 2023)
According to SNI03-6468-2000, high-strength concrete is concrete with a minimum compressive strength of 41.4 MPa. The high strength concrete is useful in precast and prestressed concrete. This study aimed to find the effect of using superplasticizer and hydrated lime on the compressive strength of high-strength concrete K-500 when reviewed at the age of 3, 7, 14, and 28 days. This study used several percentages of superplasticizer for high-strength concrete mixtures, namely the proportions of 0%, 1%, 2%, and 3%. As for the hydrated lime that was tested, the percentages were 0%, 5%, 15% and 25%. The results of the compressive strength test of K-500 concrete without superplasticizer and hydrated lime at the age of 3, 7, 14 and 28 days respectively were 208 kg/cm2, 347 kg/cm2, 462 kg/cm2, and 525 kg/cm2. This results has met the requirements for compressive strength of K-500. Using of 1% to 3% superplasticizer with 5% of hydrated lime at the age of 28 days, the compressive strength obtained were 698.67 kg/cm2, 668.89 kg/cm2, and 465.48 kg/cm2. The compressive strength of using 1% to 3% of superplasticizer with 15% of hydrated lime at the age of 28 days were 508.89 kg/cm2, 473.33 kg/cm2, and 359.70 kg/cm2. As for the compressive strength of using 1% to 3% superplasticizer with 25% of hydrated lime at the age of 28 days were 320.00 kg/cm2, 300.44 kg/cm2, and 254.22 kg/cm2. From the test results, it can be concluded that the use of 1% admixture superplasticizer and 5% hydrated lime is the most optimal mixture compared to the others, with the compressive strength test result was 698.67 kg/cm2. In addition, the author also found that  the greater percentage of using the hydrated lime in the concrete mixture could reduce the compressive strength of the concrete.